Innovative Teaching Education in Mathematics: Capacity Building Project in Higher Education funded by the Erasmus Plus Program - (:unkn) unknown (My University, 2025)
Its main objective is to improve the teaching, learning, and understanding of 1st-year Mathematics among Engineers in Europe, Israel, Kosovo, and Uzbekistan. The main tools will be employed are (a) Calculus Assisted Tools; (b) Innovative Teaching Methods; and (c) Real Life Problems that can be tackled using fundamental Mathematics taught in Calculus I and Linear Algebra I. Amaç: Avrupa, İsrail, Kosova ve Özbekistan daki seçilmiş üniversitelerde matematik dersi veren akademisyenlerin öğretme ve birinci yıllarında matematik dersi alan mühendis öğrencilerin öğrenme anlayışını geliştirmektir. Kullanılacak yöntemler: (a) Matematik öğrenmeyi ve öğretmeyi destekleyen araçlar; (b) Yenilikçi Öğretim Yöntemleri; ve (c) Calculus I ve Lineer Cebir I'i öğretirken kullanılabilecek gerçek yaşama dayalı problemler.